PENGARUH CITRA PERUSAHAAN, KUALITAS PELAYANAN, DAN PERSEPSI HARGA TERHADAP KEPUASAN KONSUMEN COFFEE (Studi Kasus pada Strada Coffee Semarang) - Arif Pambudi, 14.05.51.0228; Sutedjo, Bambang (Students' Journal of Economic and Management, 2018)
This study aims to analyze the influence of corporate image, service quality, and price perception on the satisfaction of coffee consumers. This research is a quantitative research, which uses primary data. The population in this study were all consumers of Strada Coffee Semarang Sampling was carried out using purposive sampling method. The instrument used in this study is a questionnaire distributed directly to respondents. The number of questionnaires distributed and used as further analysis material is 100. Analytical technique using tested the validity, tested the reliability, analysis of the multiple regression, F test, coefficient of determination, and t test. The results showed that the company image variable had no effect on customer satisfaction, service quality had a positive and significant effect on customer satisfaction, and price perception had a positive and significant effect on the satisfaction of coffee consumers. Keywords: corporate image, service quality, price perception, and customer satisfaction.